2016
DOI: 10.1016/j.clinthera.2016.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Aspects of Alarmin Cytokine Interleukin 33 or Its Inhibitors in Various Diseases

Abstract: The protective or exacerbated aspects of use of IL-33 or its inhibitors are dependent on the type of infection or inflammatory condition, duration of disease (acute or chronic), organ involved, cytokine microenvironment, dose or kinetics of IL-33, and genetic predisposition. The alarmin cytokine IL-33 acts at cellular, molecular, and transcriptional levels to mediate pluripotent functions in various diseases and has potential therapeutic value to mitigate the disease process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 85 publications
0
16
1
Order By: Relevance
“…In this regard, also other cytokine trap proteins, such as the recently described TSLPtrap, 47 might be interesting leads. The IL-33/ ST2 axis has also been implicated in various other non-T H 2 diseases, such as rheumatoid arthritis, colitis, multiple sclerosis, lupus, age-related macular degeneration, fibrosis, and disorders of the central nervous system, 4,48 implicating that the effect of our IL-33trap technology might be much broader than allergic diseases. Given the apparent diverse roles of IL-33 in a multitude of processes, manipulation of IL-33 signaling might be highly disease dependent.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, also other cytokine trap proteins, such as the recently described TSLPtrap, 47 might be interesting leads. The IL-33/ ST2 axis has also been implicated in various other non-T H 2 diseases, such as rheumatoid arthritis, colitis, multiple sclerosis, lupus, age-related macular degeneration, fibrosis, and disorders of the central nervous system, 4,48 implicating that the effect of our IL-33trap technology might be much broader than allergic diseases. Given the apparent diverse roles of IL-33 in a multitude of processes, manipulation of IL-33 signaling might be highly disease dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown contrasting roles of IL-33 in bone remodeling. As reported by some authors, IL-33 stops osteoclast formation from bone marrow precursor cells [99], while others showed IL-33 shifting the equilibrium in vitro from osteoclasts to the differentiation of alternatively activated macrophages [100]. A reduction in osteoprotegerin expression mediated by osteoblasts and an increase in osteoclastogenic factor release inducing bone resorption during inflammation mediated by IL-33 was proposed [101], even though some in vitro evidence suggests that IL-33 stimulates matrix mineralization [102].…”
Section: Il-33mentioning
confidence: 98%
“…There is enough evidence to show upregulated IL-33 expression by astrocytes and peripheral leukocytes in MS patients (64). Although it has been found that IL-33 induces pro-inflammatory type-2 responses, the anti-inflammatory properties of this cytokine have been thought to be beneficial in autoimmunity (65,66) as well as in many other disorders (67).…”
Section: Discussionmentioning
confidence: 99%